Diverse bioerosion structures in lower Pliocene deposits from a volcanic oceanic island: Baía de Nossa Senhora section, Santa Maria Island, Azores (central North Atlantic) - Dávid, Árpád (2021)
Pliocene body fossils from Santa Maria Island, Azores, have been studied for decades, but only more recently have ichnofossils received their due attention. Calcareous Pliocene deposits from the Baía de Nossa Senhora section contain numerous, diverse, well-preserved natural casts of invertebrate borings. The study of this type of fossils adds to knowledge on the dispersal of benthic faunas across oceans to volcanic oceanic islands. The borings belong to seven ichnogenera and twenty-two ichnotaxa at the ichnospecies level with more than half pertaining to Entobia, which is produced by clionaid sponges. Other borings found were produced by bivalves (Gastrochaenolites), polychaete worms (Caulostrepsis and Maeandropolydora), sipunculid worms (Trypanites), phoronid worms (Talpina) and ctenostome bryozoans (Iramena). The occurrence, ichnogeny, distribution and preservational state of the borings suggest that the bearing bioclasts have been exposed for several years on the sea floor. The borings derive from different bathymetric zones on the shelf, and their formation took place during several bioerosional phases. The association of borings belongs to the Entobia ichnofacies, which is typical of carbonate rocky shores, and shows close similarity to those described from the Paratethys, Mediterranean and partly the eastern Atlantic regions. This fits the idea that most of the Neogene shallow-water marine fauna in the Azores is biogeographically related to the eastern Atlantic shores.